1988
DOI: 10.1111/j.1600-0897.1988.tb00234.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Human Leukocyte Antigen‐ABC and ‐D/DR Antigens in the Unfixed Human Testis

Abstract: The distribution of the major histocompatibility complex (MHC) antigens in the unfixed human testicle was studied by indirect immunofluorescence. Three murine monoclonal antibodies to the common determinants of class I MHC antigens (human leukocyte antigen [HLA]-ABC) and three against class II MHC antigens (HLA-D/DR antigens), respectively, were utilized. No class I MHC antigens were identified on developing testicular germ cells including spermatozoa, but interstitial cells between the seminiferous tubules (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
52
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(54 citation statements)
references
References 23 publications
2
52
0
Order By: Relevance
“…However, the class II antigen was identified on dendrite-like cells between the seminiferous tubules and on vessel endothelium. Consistent with our results, Haas et al (1988) did not find MHC antigen expression in Sertoli cells and germ cells. Wilkins et al (1992) found that MHC class II and I were expressed by most stromal cells but not by seminiferous tubules in testes from pediatric subjects.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, the class II antigen was identified on dendrite-like cells between the seminiferous tubules and on vessel endothelium. Consistent with our results, Haas et al (1988) did not find MHC antigen expression in Sertoli cells and germ cells. Wilkins et al (1992) found that MHC class II and I were expressed by most stromal cells but not by seminiferous tubules in testes from pediatric subjects.…”
Section: Discussionsupporting
confidence: 82%
“…In the adult, Haas et al (1988) described the absence of MHC class I and II antigens in developing testicular germ cells, including spermatozoa MHC class II antigens were not found on any cells within the seminiferous tubules. However, the class II antigen was identified on dendrite-like cells between the seminiferous tubules and on vessel endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…Because germ line cells are devoid of MHC molecules, they do not display antigenic peptides at their surface, and therefore peptides encoded by cancergermline genes are strictly tumor-specific. 7 A number of clinical trials of therapeutic vaccination have been initiated, based on the use of defined antigens encoded by cancer-germline genes. 8 -13 A minority of patients showed regression of metastatic tumors after vaccination with various antigen forms.…”
mentioning
confidence: 99%
“…These MA are expressed by tumors of different histology and not by normal cells with the exception of spermatocytes and spermatogonia (16). These latter cells do not express HLA class I molecules, and, therefore, the host immune system is not exposed to these MA in nontumor-bearing individuals (17). Among them, those that appear to exert a predominant role are those coded by the MAGE-A family of genes (18).…”
mentioning
confidence: 99%